PENELITIAN TINDAKAN KELAS (PTK) MODEL KURT LEWIN UNTUK MENINGKATKAN MINAT BELAJAR SENI BUDAYA SISWA SMA NEGERI 13 MAKASSAR - Nelsa, Nelsa (Universitas Negeri Makassar, 2025)
The background of this study is the low interest in learning among students in cultural arts education classes. Many students feel unmotivated and lack enthusiasm for learning due to unengaging and unimpressive teaching methods, which result in students being passive during the learning process. Therefore, this study aims to enhance students' interest in learning cultural arts by implementing engaging, varied, and innovative teaching methods for tenth-grade students of SMAN 13 Makassar. This study employs Penelitian Tindakan Kelas (PTK), which involves a series of activities including planning, implementation, reflection, and follow-up. The research data were collected through student questionnaires and direct observation of the learning process. The findings reveal a significant improvement in students' interest in learning cultural arts following the application of engaging teaching methods. The percentage of student engagement increased from 32% in the pre-cycle phase to 59% in cycle I and reached 87% in cycle II. These findings confirm that implementing engaging teaching models can be an effective strategy to enhance students' interest in learning cultural arts.